2021
DOI: 10.1038/s41467-021-25337-5
|View full text |Cite
|
Sign up to set email alerts
|

SCOPE enables type III CRISPR-Cas diagnostics using flexible targeting and stringent CARF ribonuclease activation

Abstract: Characteristic properties of type III CRISPR-Cas systems include recognition of target RNA and the subsequent induction of a multifaceted immune response. This involves sequence-specific cleavage of the target RNA and production of cyclic oligoadenylate (cOA) molecules. Here we report that an exposed seed region at the 3′ end of the crRNA is essential for target RNA binding and cleavage, whereas cOA production requires base pairing at the 5′ end of the crRNA. Moreover, we uncover that the variation in the size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 73 publications
0
77
1
Order By: Relevance
“…It was observed that 40% of the studies were conducted in the USA only [ 14 , 15 , 25–28 ], 13% in Canada [ 29 , 17 ] and China [ 2 , 30 ] each. Apart from this, some studies have been conducted in Germany [ 31 ], Singapore (Ooi et al, 2021[ 32 ]), Netherlands [ 18 ], Japan [ 33 ], and Saudi Arabia [ 34 ], representing 7% each from included studies ( Figure 2 ). Patient’s details have not been specified in any of the articles, although the type of specimen taken for most of the studies was nasopharyngeal swab (n = 10) [ 14 , 25 , 26 , 2 , 13 , 17 , 18 , 27 , 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that 40% of the studies were conducted in the USA only [ 14 , 15 , 25–28 ], 13% in Canada [ 29 , 17 ] and China [ 2 , 30 ] each. Apart from this, some studies have been conducted in Germany [ 31 ], Singapore (Ooi et al, 2021[ 32 ]), Netherlands [ 18 ], Japan [ 33 ], and Saudi Arabia [ 34 ], representing 7% each from included studies ( Figure 2 ). Patient’s details have not been specified in any of the articles, although the type of specimen taken for most of the studies was nasopharyngeal swab (n = 10) [ 14 , 25 , 26 , 2 , 13 , 17 , 18 , 27 , 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The combination of VmeCmr and NucC with an optimal guide RNA and fluorescence readout provided a LoD of 2 fM for detection of the SARS-CoV-2 N gene transcript, consistent with the observation that a reaction with fewer than 1 × 10 5 copies of the viral RNA (8 fM) can be readily detected (Figure 8 ). This compares with a LoD using the T. thermophilus Csm (TtCsm) system of 1 × 10 7 copies (100 pM) ( 40 ) and 1.2 × 10 8 copies (1 nM) detected by the TtCmr system ( 41 ). The >100-fold higher sensitivity of the assay we describe here is likely due to a combination of factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the collateral cleavage activities of Cas12 and Cas13 have been repurposed for the development of rapid and specific assays capable of detecting specific RNA or DNA sequences ( 36–39 ). Two recent studies have demonstrated that the ability of type III (Cas10) CRISPR systems to detect RNA specifically and synthesise cOA can be harnessed in combination with CARF family effector nuclease Csm6 to provide an alternative assay system ( 40 , 41 ). Here, we demonstrate that a prophage-encoded Vibrio type III-B system generates cA 3 on specific target RNA binding, resulting in the activation of the NucC effector nuclease for non-specific dsDNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…An example of such apparently incomplete system is the Type III-B CRISPR-Cas system of Thermus thermophilus , whose Cas10 protein lacks the HD domain [ 43 ]. However, since Cas10 possesses an intact Palm domain, it is still capable of activating auxiliary effectors via the cOAs pathway [ 44 ]. The Type III-B locus of T. thermophilus encodes a cOA-activated DNA nickase, which might be responsible for the plasmid degradation in the absence of the Cas10 HD DNase activity [ 45 ].…”
Section: History Of Type III Crispr-cas Researchmentioning
confidence: 99%